Job Evaluation and Wage Setting in the Public Sector of Israël - Harel, Gedaliahu (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1976)
This paper examines the Israeli experience with spectoral job evaluation and incomes policy analysis, and the causes for the abortive attempt.